PENGARUH METODE SUKU KATA TERHADAP KETERAMPILAN MEMBACA PADA MATA PELAJARAN BAHASA INDONESIA PESERTA DIDIK KELAS 1 SDN 24 PALU - Purniandari, Lita; Narayati, Putu Satya; Putrayasa, I Wayan Budiagus (STAH Dharma Sentana Sulawesi Tengah, 2024)
The aim of this research is to determine the effect of the syllabic method on reading skills in Indonesian language subjects for class 1 students at SDN 24 Palu. Determining the sample in this study used a purposive sampling technique. The method used is quantitative with research type One-group Pre-test-Post-test Design with data collection techniques used, namely observation, validation, tests, questionnaires and documentation. From the results of the hypothesis test, the tcount value is 9.173 and the ttable value is 1.703, so the tcount value is greater than the ttable value. So that Ho is rejected and H1 is accepted, then there is an influence of using the syllable method on reading skills in Indonesian language subjects of class 1 students at SDN 24 Palu. In the learning process using the syllable method in this research, students received 8 good responses and 20 very good responses with an average score of 88,21%.